Penentuan Karyawan Teladan Pada PT. Jiangmen Electronics Indonesia Menggunakan Metode Simple Additive Weighting - Norma Yunita; Imron Maulana; Siti Marlina (Paradigma - Jurnal Komputer dan Informatika, 2022)
In making decisions for exemplary employees, PT Jiangmen Electronics Indonesia uses several methods, namely taking an assessment of the attendance every three months, and individual assignments given by the supervisor. The data obtained after that must be reprocessed into an assessment to produce exemplary employee decisions. Data is collected for collection from the types of criteria such as assessment of attendance, work results, work efficiency, working time, work behavior, from the results of the combined assessment, will be processed manually with a data processing application from Microsoft Excel. The appropriate data will be given directly to the head of the section for selection of exemplary employees. The existence of the Simple Additive Weighting (SAW) method can determine with many criteria in making an exemplary employee appraisal decision and the time required for data processing will also be faster and more efficient. The purpose of this study is to assist companies in the process of selecting exemplary employees. For the largest value on the absenteeism criteria is alternative A1 or employees on behalf of Bambang, for the largest value on the work results criteria is alternative A18, the selected employee is Andy, while for the criteria for work efficiency the largest value on alternative A19 or the selected employee is Riky, for the greatest value with the criteria of working time on alternative A5 the selected employee is Irfan and for the largest value of the criteria for work behavior on alternative A2 the selected employee is Imron.